Reconstructing Legal Protection for Child Victims of Neglect under Law No. 23 of 2004 on the Elimination of Domestic Violence in Indonesia - Syarifuddin, Syarifuddin; Wajdi, Farid; Gultom, Arifin (Hukum Keluarga Islam IAIN LANGSA, 2025)
Violence against children is extremely dangerous and must be addressed immediately. Therefore, scientific research is needed on the reconstruction of legal protection for child victims of child neglect under Law No. 23 of 2004. The issue to be discussed is how to reconstruct legal protection for child victims of child neglect crimes under Law No. 23 of 2004 on the Elimination of Domestic Violence. Previous research has discussed the reconstruction of legal protection for children who have come into contact with the law after diversion based on the principle of justice. This research focused on reconstructing specific regulations on the protection of children who have committed criminal offenses after diversion while maintaining the principle of justice. This study differs in that it focuses on the reconstruction of legal protection for children as victims of child abandonment crimes based on Law No. 23 of 2004. The purpose of this study is to provide solutions to research problems concerning the concept of legal protection of children from child neglect crimes. The research method used is normative legal research through a conceptual approach and a legislative approach. Through this research method, the results obtained indicate that children's rights must be properly considered and protected through criminal law and legislation. Research findings on the reconstruction of legal protection for child victims of child neglect based on Law No. 23 of 2004 on the Prevention and Handling of Domestic Violence indicate that the protection of children's rights remains a top priority. This research emphasizes the need for commitment from all law enforcement officials and the community to jointly enforce legal provisions to protect Indonesian children from neglect and violations of children's rights based on justice for children and human values.